A headspace-gas chromatography method for isopropanol determination in warfarin sodium products as a measure of drug crystallinity - Rahman Ziyaur; Akhtar Sohail; Siddiqui Akhtar; Ciavarella Anthony B.; Nguyenpho Agnes; Faustino Patrick J.; Khan Mansoor A. (Acta Pharmaceutica)
Coumadin® a nd s everal generic products of warfarin s odium (WS) contain the crystalline form (clathrate) in which WS and isopropanol (IPA) are associated in a 2:1 molar ratio. IPA is critical in maintaining the WS crystalline structure. Physicochemical properties of the drug and drug product may change when the crystalline drug transforms to amorphous form. A headspace-gas chromatography (HS-GC) method was developed and validated for IPA determination in the WS drug product. n-propanol (NPA) was used as internal standard and the method was validated for specificity, system suitability, linearity, accuracy, precision, range, limits of detection and quantification, and robustness. The method was specific, with good resolution between IPA and NPA peaks. Chromatographic parameters (retention time, IPA/NPA area ratio, tailing factor, theoretical plates, USP symmetry, capacity factor, selectivity and resolution) were consistent over three days of validation. The analytical method was linear from 2-200 μg mL-1 (0.1- 10 % IPA present in the drug product). LOD and LOQ were 0.1 and 2 μg mL-1, respectively. Accuracy at low (2 μg mL-1) and high (200 μg mL-1) IPA concentrations of the calibration curve was 103.3-113.3 and 98.9-102.2 % of the nominal value, resp. The validated method was precise, as indicated by the RSD value of less than 2 % at three concentration levels of the calibration curve. The method reported here was utilized to determine accurately and precisely the IPA content in in-house formulations and commercial products. In summary, IPA determination by HS-GC provides an indirect measure of WS crystallinity in the drug product. Nevertheless, it should be confirmed by another analytical method since IPA from the drug substance is not distinguishable from IPA that may be present outside the drug crystals in a dosage form when prepared by wet granulation with IPA.